ANALYSING THE INFLUENCE OF INTERNET CELEBRITY SHORT VIDEOS ON VIEWER BEHAVIOUR: BEAUTY AS A PERSUASIVE FACTOR - Redjeki, Finny; Aripin, Zaenal; Ruchiyat, Endang (KRIEZ ACADEMY : Journal of development and community service, 2024)
This study investigates the influence of short videos by internet celebrities on consumers' perceptions and behavior towards beauty products, with a focus on the authenticity and credibility factors of influencers. The use of social media and platforms like TikTok, Instagram, and YouTube have changed the digital marketing paradigm, with beauty influencers playing a key role in influencing consumer preferences and purchasing decisions. This analysis integrates psychological theories such as identification with influencers, consumer motivation, and information processing processes to understand the mechanisms underlying the influence of these short videos. Influencer authenticity, which includes consistency in product recommendations and transparency in interactions with followers, was identified as a crucial factor in building consumer trust. Research shows that this authenticity not only strengthens the emotional bond between influencers and followers, but also strengthens the persuasive impact of the beauty messages conveyed. Additionally, an influencer's credibility, which is often tied to their reputation and experience in the beauty industry, plays an important role in increasing followers' appeal and acceptance of the products being promoted. The results of this study show that a successful influencer marketing strategy in the beauty industry must consider integrity and transparency as the main pillars. Brands should strive to build ongoing collaborations with influencers who have aligned values and prioritize honesty in conveying product information to their followers. Meanwhile, influencers need to pay attention to honesty in recommending products in order to maintain their credibility in the long term. This research provides valuable insights for marketing practitioners to optimize influencer marketing strategies in the dynamic beauty context. By understanding the role of authenticity and credibility in influencing consumer attitudes and behavior, brands can leverage the positive influence of influencers to build strong relationships with their audiences and achieve more effective marketing goals.